(untitled) (Journal of Nepal Geological Society, 2024)
Geological mapping of the granite body along the Kulekhani-Palung area was carried out and the geological boundary of the granite body was well-traced out in 1:25,000 scales. This study investigates the mineralogical and textural characteristics of the Palung Granite, located in the Lesser Himalaya region of central Nepal, with the primary objective of classifying the granitic massif. Field observations, hand sample analysis, binocular observation of individual grains and thin section studies were carried out to assess the mineralogy and texture of the rocks. The Palung massif reveals four distinct types of granites, each showing diverse mineralogical compositions and textures. These granites contain various minerals, including quartz, orthoclase, plagioclase, muscovite, biotite, and tourmaline. Through mineralogical analysis, the granites within the Palung massif were identified as coarse-to-medium-grained quartz-rich granite and pegmatites, coarse-grained feldspar-rich granite with biotite and tourmaline, coarse-to-medium-grained muscovite-tourmaline granite, and coarse-grained biotite-tourmaline granite with a porphyritic texture. Classification according to the QAP system of the International Union of Geological Sciences (IUGS) categorizes these granites into quartz-rich granitoid, monzogranite, granodiorite, tonalite, and quartz monzodiorite. The contact between the granite and surrounding country rocks varies from sharp to irregular.